Information contracting tools in a cancer specialist unit:the role of Healthcare Resource Groups (HRGs) - Carol Marlow; Hugh Preston (Information Research: An International Electronic Journal)
The need for high quality management information within the contracting process has driven many of the major developments in health service computing. These have often merged clinical and financial requirements, usually along patient-centred lines. In order to identify a common currency for a range of clinical activities that are inherently variable, price tariffs have been drawn up on the basis of 'episodes of care' within specialties. Healthcare Resource Groups (HRGs) were designed to meet the need for a common information currency. However, they were designed for acute care. The study on which this paper is based aims to examine their applicability to chronic care in a cancer specialist unit. The data were drawn from the patient information system within a major cancer unit. The focus of the investigation is encapsulated in the following questions: a) Do HRGs really work as a grouping and costing methodology? b) How relevant are HRG classifications for long-term patient care? The investigation demonstrated that not all HRGs are iso-resource within this environment. The findings from the data analysis are echoed by the NHS Executive's own evaluation . This does not negate advantages in their use. Furthermore, the development of Health Benefit Groups as information management tools, through a focus on health conditions and interventions rather than on purely on treatments, offers potential for greater validity within a chronic care situation.